Pharmacology and Pharmacotherapeutics - R.S Satoskar (Popular Prakashan Pvt. Ltd. / Elsevier, 2017)
The 25th revised edition of Pharmacology and Pharmacotherapeutics continues to maintain its status as an up-to-date, accurate and reliable text for medical students as well as practicing physicians. The advances in molecular biology have significantly influenced the understanding of pathogenesis of diseases and development of newer drugs. The real challenge, however, remains in application of the available information while treating a patient. This book has always placed before the readers an integrated approach intertwining current knowledge of pathophysiology of the disease, pharmacology of available drugs and strategies for medical management of diseases. The current edition balances the complexity and simplicity of scientific content to provide students of medicine and/or pharmacy an insight into rational therapeutics. It gives several practical tips which empowers the physician to treat patients effectively and confidently. Written in an integrated fashion, Pharmacology and Pharmacotherapeutics builds up a strong foundation of scientific knowledge to guide decision making and to promote a holistic approach towards patient care in clinical practice. Emphasis on Clinical Pharmacology in each chapter Current guidelines for therapeutic decisions Newer sedatives-hypnotics Hypertension management: Updates Advances in treatment of obesity and hyperlipidemia Newer antiepileptics Antiviral agents for hepatitis C Rheumatoid arthritis: pharmacotherapy Management of pulmonary hypertension Newer antidiabetic drugs Advances in immunotherapeutics Vitamin D and calcium: Updates Therapeutic advances for infectious diseases